SOCIAL MEDIA Y ESTRATEGIAS DE COMUNICACIÓN DE LAS REDES SOCIALES EN EL SECTOR HOTELERO DE LA COMUNIDAD DE MADRID - Dda. Gemma CASCALES GARCÍA,Dra. Trinidad CORTÉS PUYA,Dra. María GALMÉS CEREZO (Fonseca, Journal of Communication, 2023)
Social networks within social media are provoking substantial changes in communication strategies within the hospitality industry. New professional profiles emerge linked to social networks management and customer behaviour data analysis. These new professionals have influence on the definition of communication strategies. Hotels are forced to adapt to this new social reality, and to incorporate new technologies into their social communications strategies. Hotels require to offer their users/consumers a direct, transparent and quickly response to the needs that the clients demands.